Factors That Influence the Persistence of Company Profits in Manufacturing Companies Listed on the Indonesian Stock Exchange - Huda, Ihsanul; Winarsih, Winarsih (Husnayain Business Review, 2024)
Financial statements are a tool for management to convey information about the company's economic and financial performance for users of financial statements, both internal and external parties. The income statement is part of the financial statements that present the profits earned by the company during a certain period. Information about earnings has an important role for parties with an interest in the company. The population in this study are companies listed on the IDX. The sample in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique that will be used in this research is purposive sampling. The analytical tool used is Multiple Linear Regression. Based on the results of the study, it can be concluded that cash flow volatility has a negative effect on earnings persistence, managerial ownership has a positive effect on earnings persistence, while sales volatility, debt levels, institutional ownership, and firm size have no effect on earnings persistence.